2010
DOI: 10.1021/ja909562y
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Regioselectivity and Alkene-Directing Effects in Nickel-Catalyzed Reductive Couplings of Alkynes and Aldehydes

Abstract: Origins of regioselectivity and alkene-directing effects in nickel-catalyzed reductive coupling reactions were investigated by density functional calculations. Regioselectivity of simple alkynes is controlled by steric effects, while conjugated enynes and diynes are predicted to have increased reactivity and very high regioselectivities, placing alkenyl or alkynyl groups distal to the forming C–C bond. The reactions of enynes and diynes involve 1,4-attack on the conjugated enyne of the Ni-carbonyl complex on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 84 publications
(31 reference statements)
3
42
0
Order By: Relevance
“…The 2.0 kcal mol −1 difference between the activation barriers in the regioisomeric cyclopropanation and the ring expansion of TSs (TS6a and TS9a) suggests a regioselective ratio greater than 20 : 1 (m-terphenylo-terphenyl). 24 This computed result is consistent with experimental results. DFT computation for the energy surface in the proposed pathways for the PtI 2 -catalyzed cyclization of ACE b, which bears a Me group at the C1-position, was also carried out (see Scheme S2 †).…”
Section: Resultssupporting
confidence: 90%
“…The 2.0 kcal mol −1 difference between the activation barriers in the regioisomeric cyclopropanation and the ring expansion of TSs (TS6a and TS9a) suggests a regioselective ratio greater than 20 : 1 (m-terphenylo-terphenyl). 24 This computed result is consistent with experimental results. DFT computation for the energy surface in the proposed pathways for the PtI 2 -catalyzed cyclization of ACE b, which bears a Me group at the C1-position, was also carried out (see Scheme S2 †).…”
Section: Resultssupporting
confidence: 90%
“…With respect to regioselectivity, in 2010, Houk and co-workers showed that the selectivity of simple alkenes is controlled by steric effects, 313 whereas for conjugated diynes or eneynes, the calculations (at the B3LYP/6-31G(d)(LANL2DZ) level of theory) suggested that the observed regioselectivity may originate from a mechanism involving a 1,4-attack pathway that is stabilized by a π-Ni interaction and has less distortion in the transition state (relative to other possible mechanism).…”
Section: Heckmentioning
confidence: 99%
“…However, the use of ligand 4 (SIPr) reverses selectivity, favoring regioisomer 8 with 81:19 regioselectivity. We next examined a conjugated enyne, knowing that this substrate class is one of the most biased alkyne classes in reductive couplings 3d–f,6. Standard coupling with ligand 3b (IMes) provided highly selective coupling at the aliphatic substituted alkyne terminus to produce isomer 7 as anticipated (entry 6).…”
mentioning
confidence: 96%
“…Previous results from our lab illustrated that regioselectivities may be moderately impacted by ligand structure, but the effects were too small to be broadly useful 5. A recent computational study described the minimal impact that ligand structure has on regioselectivity in aldehyde-alkyne reductive couplings with Ni(0)-phosphine catalysts and organoborane reducing agents,6 thus highlighting the complexity of designing a ligand-controlled regioselective process. Herein, we describe that carefully selected carbene ligands complexed with nickel provide a general solution to regiocontrol in silane-mediated aldehyde-alkyne reductive couplings with a broad range of alkynes.…”
mentioning
confidence: 99%